Prevalence of Obesity and Associated Risk Factors among Rural Adult Population of Puthia Upazilla, Rajshahi (TAJ: Journal of Teachers Association, 2023)
Introduction: Obesity is a major public health concern in Bangladesh, driven by socioeconomic factors, lifestyle choices, physical activity levels, and demographics. The influence of technology and industrialization has disrupted behavioral patterns among rural residents, leading to increased susceptibility to weight gain and non-communicable diseases. To gain precise insights, a cross-sectional study was conducted to assess the prevalence of obesity and identify specific risk factors among rural adults.Methods: From September to November 2022, this study was carried out at the Rajshahi Medical College's Department of Community Medicine. Data were gathered by conducting face-to-face interviews with the rural adult population of Puthia Upazilla, Rajshahi, aged 18 to 59.In all, 548 people from Rajshahi's Puthia Upazilla took part in the survey.Result: In this study, respondents had a mean age of 38.84 (±12) years. About 39.78% were overweight, and 14.23% were obese based on BMI. The mean BMI was 25.07 (±5.17) kg/m². Around 20.9% of males and 27.9% of females had a higher risk based on waist-hip ratio. Approximately 43.6% were highly active, while 36.86% had low physical activity levels. About 1.6% reported taking anti-depressant drugs. Around 31.4% consumed fried food 1 to 3 times weekly, and 35.2% drank milk occasionally. Regarding salt intake, 32.1% added salt daily to their meals. The relationship between physical activity and BMI (p